The Correlation Reading Habit and Vocabulary Mastery with Listening Skill in English (Correlational study islamic Senior High School Student in As-Syafiiyah 02 Pondok Gede) - Nurchurifiani, Eva (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2016)
The objective of the research is to determine the relationship between (1) reading habit and listening skill in English, (2) vocabulary mastery and listening skill in English, and (3) reading habit together with vocabulary mastery and the studentsâ English listening skill. The research was conducted in As-syafiâiyah Islamic Senior High School (SMA Islam As-syafiâiyah 02 Pondok Gede). The population of the research is all students in As-syafiâiyah Islamic Senior High School. The sample used 30 students who selected randomly. The technique for analyzing the data was the statistical technique of correlation and regression. The results of the research are as follows: (1) there is a positive correlation between reading habit and listening skill, with coefficient correlation (rx1y) = 0,646 and the regression equation Å¶ = 5,742 + 0,152X1. The coefficient of determination yielded is (rÂ²) = 0,416. It means that 41,6% of the listening skill in English is determined by reading habit. (2) there is a positive correlation between vocabulary mastery and listening skill in English, with coefficient correlation (rx2y) = 0,764 and the regression equation Å¶ = 6,161 + 0,657X2. The coefficient of determination yielded is (rÂ²) = 0,583. It means that 58,3% of the listening skill in English is determined by vocabulary mastery. (3) there is a positive correlation between reading habit, vocabulary mastery and listening skill, with coefficient correlation (Ry1.2) = 0,791 and the regression equation Å¶ = 3,613 + 0,063X1 + 0,510X2. The coefficient of determination yielded is (RÂ²) = 0,626. It means that 62,6% of the studentsâ English Listening skill is determined by reading habit and vocabulary mastery. Therefore, from the result of this research it can be concluded that studentsâ English listening skill can be enhanced by increasing studentsâ reading habit and vocabulary mastery either individually or simultaneously.